Macrocytosis is highly prevalent in Raebareli district, Uttar Pradesh, India - Gupta, Ankit; Gani, Mohd. Usman; Kumar, Pramod (International Journal of Research in Medical Sciences, 2020)
Background: Anemia is a most common health issue in Indian population mainly due to nutritional deficiencies. A number of factors contribute in anemia which is further categorized based on various parameters in hematological indices and microscopic examination. Methods: A retrospective study has been carried out on the patients (n = 1332) in a retrospective study on the patients (n = 1332) in Raebareli district to determine prevalence of anemia and subsequent categorization into normocytic, microcytic and macrocytic based on complete blood count (CBC) profile and blood smear. Results: This study demonstrates 15.54% patients were diagnosed for anemia and more than half of the total anemic patients (55.07%) were found to be suffered from macrocytosis which was found significantly more prevalent among male (65.17%) compare to female (38.38%) patients. Conclusions: Several factors may contribute to macrocytosis among male population including alcoholism in Raebareli region. However, female patients were found almost equally susceptible to all three forms of anemia: normocytic, microcytic and macrocytic. This study provides a key insight into prevalence and possible causes of different types of anemia in this region which may be useful for implementation of government health programs to counter this problem and provide better treatment plans.